Theophrastus on the Origin of Music - Ritoók, Zsigmond (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XL-XLI (2004-2005). At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.